PENENTUAN PENERIMA BERAS RASKIN DI KELURAHAN OESAPA BARAT MENGGUNAKAN METODE K-NEAREST NEIGHBOR (KNN) - yampi kaesmetan (Jurnal Teknologi Terpadu, 2016)
Rapid technological developments are currently very influential in all areas of work especially in the field ofmapping the location on maps online. Village of West Oesapa, District Kelapa Lima, Kupang is one of thevillages that aspires for the welfare of the community by way of distribution of poor rice aid to the poor in theeconomic field. Raskin rice distribution should be shared equitably and meets the criteria as a poor ricerecipient in the Village of West Oesapa. With KNN method (K-Nearest Neighbor) will count how many people ineach neighborhood would receive help poor rice in accordance with existing criteria, and to determine thepercentage can be seen in the form of a map.